Synthesis and Evaluation of an Enantiomerically Enriched Bifunctional Chelator for 64Cu‐Based Positron Emission Tomography (PET) Imaging. Issue 6 (15th January 2014) - Chong, Hyun‐Soon; Sun, Xiang; Zhong, Yongliang; Bober, Kamil; Lewis, Michael R.; Liu, Dijie; Ruthengael, Varyanna C.; Sin, Inseok; Kang, Chi Soo
Abstract: We report the synthesis and evaluation of an enantiomerically enriched bifunctional chelator, ( S )‐ C ‐NE3TA. The bifunctional chelator was efficiently prepared by regioselective and stereoselective ring opening of an aziridinium ion. The new chiral chelator instantly and almost completely bound to 64 Cu at room temperature. The corresponding 64 Cu‐radiolabeled complex remained intact in human serum for 48 h without any measurable transchelation and was tolerant to a rigorous EDTA challenge for 24 h. The 64 Cu‐radiolabeled ( S )‐ C ‐NE3TA complex was stable in mice and produced an excellent biodistribution profile. The results of the in vitro and in vivo evaluations indicate that the new optically active chelator is a promising candidate for PET imaging applications. Abstract : We report an enantiomerically enriched bifunctional ligand in the NE3TA series for the first time. The chelator instantly bound to 64 Cu to form a complex that was stable in vitro and in vivo and possesses great promise for use in targeted positron emission topography (PET) imaging.